Integrated input-output analysis of the economic impact of higher oil price in Malaysia - Abdul Hamid, Khalid (2010)
The global increase in crude oil prices since 2003 onwards has had negative consequences on countries dependent heavily on oil imports. In contrast, oilexporting countries, although receiving a positive impact, also faced adverse effects. With increasing oil demand for imports and at the same time as declining oil supply for exports, rising oil price has exerted more pressure on the current oil consumption activities manifested in almost every form of modern living in Malaysia. Despite gaining more income and revenue from rising oil prices, the country's economy will be susceptible to the rapid increase in oil consumption and lowering of oil production, resulting in imbalances of interindustry performances as well as affecting the well-being of its households. Realizing the problems faced by these economic agents in times of rising oil prices, the government has endeavored to minimize their difficulties and burden mainly by subsidizing a portion of the domestic petrol price making it the lowest possible. This has caused petrol prices at local pump stations to be the cheapest amongst Asean countries excluding Brunei. Overlooking this benign step, the government has not heeded the root problems regarding particularly the vulnerability of oil importation and increase in cost of production. In addition, the low petrol price has distorted the local market with wastages, hoarding, smuggling, panic buying and countless others that particularly put forth more burden to producers and household using considerable oil inputs proportion in their daily activities. Meanwhile many renowned researchers such as Bacon and Kojima (2004) opined that higher crude oil price could seriously impact a country over a longer time. In keeping fuel prices low, it may rapidly inflate the government's budget and deplete oil reserves sooner than is expected. While oil production gradually declines corresponding to the ever-expanding oil consumption, relatively small oil stocks and deposits may threaten the economy's vulnerability. Such huge amounts of subsidy cost will not only disrupt efforts in promoting efficiency and diversification to succeed from high energy price as viewed by Park (2004), but deviate itself from the market's general equilibrium as debated amongst many researches in the oil literature. The study tries to achieve its objectives in examining the impact of oil price increase on the country's susceptibility, interindustry performances and distributional welfare effect. The integrated 1-0 analysis assumes other things fixed, an increase of US$1 of crude oil price will directly generate an output of 0.0448 percent. Therefore, an increase of US$60 will result a positive output amounting RM47 billion. A lower net positive gain was empirically evident in the dependency analysis comprising a declining trend of SSR, lowering OVI and high EEEI for Malaysia. Although positive overall results is gained, a detail analysis by multiplier, linkages and leakages expose a larger net impact of oil price increase compared with the previous oil crisis. The Leontief's modified price system proves the economy in the 2000s to be less susceptible than in the 1970s. Many claimed that this success was due to public policies in increasing efficiency and diversification, but our analysis proved this is inadequate since the success could be influenced by temporary effects of entry and exit of industries. As such, introduction of Goods and Services Tax (GST) is a good move to encourage optimality. Simulation of 40 sectors of the Malaysian economy reveals that 22 sectors have relative measure less than one, whilst 18 other sectors have ratios more than one but constitute less than 38 percent of GOP. This confirm of less susceptibility and the vast potential to increase efficiency and diversification. The leading oil sector, Petrol & coal products sector is still a key sector in backward and forward linkages, even more in leakages results. As a leading sector extensively used by other sector, and ranked the highest in leakages since it imported the highest inputs of oil in order to satisfy its production system, it is most beneficial to ensure it is manage efficiently particularly in critical times confronting bottlenecks and soaring temporary consumption during oil price hike. Findings on regressive income distribution pattern indicate a pro-rich strategy is more practiced compared to pro-poor. This reflects an imbalance economic policy that demands a more targeted programme to protect the poorest of households. Therefore, to insulate the most. vulnerable group, a subsidy system based on incremental oil-consumption directed only to qualified and targeted low income earners must be emulated. In terms of welfare effects on food, a glaring dissimilarity was found between the high costs of marketing or FMCI of 1.483 in Malaysia compared with only 1.06 by the US. This is due to loose interconnectedness and dependence on imported inputs. To rectify this, a niche in cluster of food production with competitive world-class standard should be created and promote oil dependent sectors to optimize their oil utilization and efficiency to upgrade the country's industrial and marketing chains. In conclusion, analogous to the general equilibrium theory and supported by our analysis and findings, we reckon that the main objectives have been met. The study shows that the oil sector is still leading and a significant sector within the economy's having less susceptibility now but has weaken over time, sharing of burden between the economic agents as well as appropriate and targeted measures overcoming welfare effects. This should serve as a guide to better manage and sustained oil resources efficiently to eschew the negative effects of oil price increase in the future.